Exploration of Accountability as a Mediator between Managerial Competencies and Supply Chain Performance of Relief Aid Organisations in Western Uganda - Aryatwijuka, Wilbroad; Frederick, Nsambu Kijjambu; Rukundo, Aloysius; Kamukama, Nixon (Business and Management Studies, 2022)
The study investigated whether accountability mediates the relationship between managerial competencies and the supply chain performance of relief aid organizations in western Uganda. A cross-sectional and correlational design was used involving a sample of 108 relief aid organizations operating in western Uganda. Organizations were stratified according to the humanitarian clusters of food security, logistics, education, water and sanitation, health, and education. Self-administered questionnaires were used to collect primary data. Data were analysed using SPSSv22, while mediation was tested using Analysis of Moments Structure (AMOS) v22 software. Accountability was found to partially mediate the association between managerial competencies and supply chain performance in relief aid organizations in western Uganda. A mediation effect of accountability in the relationship between managerial competencies and supply chain performance was tested. Previous studies tended to focus on direct relationships between the aforementioned variables. The current study enriches literature, especially in the developing country’s context and more so in the downstream of the supply chain. Future studies could take a longitudinal approach since the current study was cross-sectional. The study guides humanitarian actors to recruit staff with managerial competencies to ensure transparency and effectiveness in the delivery of relief activities hence achieving the desired supply chain performance.
Keywords: Accountability; Managerial competencies; Performance; Supply chain